ҚАРАҚАЛПАҚСТАННЫҢ ҚОҢЫРАТ ҲӘМ МОЙНАҚ РАЙОНЛАРЫ ҚАЗАҚЛАРЫ ТИЛИНДЕГИ БАЛЫҚШЫЛЫҚҚА БАЙЛАНЫСЛЫ КӘСИБИЙ СӨЗЛЕР - Куттымуратова, Ы. (FAN va JAMIYAT, 2017)
The article is devoted to the analysis of professional words connected with fishing in Kazakh language of Kungrad and Moynakh regions of Karakalpakstan. The author of the article takes into account the viewpoints of the famous scholars- lexicologists and dialectologists. The words and word combinations in fishing are compared with words and expressions of other territories. The ct professionalizm in Kazakh of Kungrad and Moynak regions are divided into such groups as dialect professionalizms whit literary equivalents and without them.